Alternative distribution to estimate the Dose – Response model in bioassay excrement - رشيد ظافر حسين; الدوري انتصار عريبي (Journal of Economics and Administrative Sciences, 2007)
Alternative distribution to estimate the Dose – Response model in bioassay excrement This research concern to study five different distribution (Probit , Logistic, Arc sine , extreme value , One hit ), to estimate dose –response model by using m.l.e and probit method This is done by determining different weights in each distribution in addition find all particular statistics for vital model .